The Global Crisis of Commodity Glut During the Second World War. Issue 6 (2nd November 2021) - Martin, Jamie
Abstract: This article examines the global crisis of commodity glut that came in the wake of the Fall of France and Italy's entry into the Second World War in June 1940, when the extension of the British blockade and shipping problems cut off primary producers around the world from major continental European markets. As a surplus of unmarketable primary commodities piled up in British colonies, as well as in Latin America and French, Dutch, and Belgian colonies, this jeapordized the blockade and threatened political unrest across the British Empire,  as well as the spread of Nazi influence in Latin America. This article examines how the British government attempted to respond to this crisis, both unilaterally and in combination with the U.S. government. In doing so, it argues that Anglo-American negotiations over a joint approach to the problem of commodity glut led to some of the earliest attempts to create new international economic organizations for the postwar period. While these plans were transformed as the surplus problem itself changed in late 1941, they nonetheless laid the groundwork for Anglo-American relief planning, contentious negotiations over an international wheat agreement, and international commodity price stabilization schemes.